Progressive integrative crop managements increase grain yield, nitrogen use efficiency and irrigation water productivity in rice - Yu, C. (2020)
This study investigated if progressive integrative crop management technology in rice (Oryza sativa L.) could improve agronomic and physiological performances, and consequently, increase grain yield, NUE and IWP. A japonica rice cultivar and an indica-japonica hybrid rice cultivar were grown in the field, with five crop managements including an unfertilized 0 N treatment (0 N), local farmer’s practice (LFP), integrative crop management (ICM) 1–3 ((ICM1, ICM2, and ICM3)). The results showed that, when compared to LFP, the ICM could not only increase grain yield, NUE and IWP, but also improve agronomic and physiological performances. Both ICM1 and ICM2 increased economic benefit. The results suggest that the integrative and optimized crop management could achieve the dual goal of increasing grain yield and resource use efficiency through improving agronomic and physiological performances, especially increases in sink size and shoot and root growth, leading to higher grain yield, NUE, and IWP.